Understanding the invisible workforce: lessons for general practice from a survey of receptionists - Ian Litchfield; Michael Burrows; Nicola Gale; Sheila Greenfield (BMC Primary Care, 2022)
Abstract Introduction The significance of the role of receptionists during the recent shift to remote triage has been widely recognised and they will have a significant role to play in UK general practice as it continues to cope with a huge increase in demand exacerbated by the COVID-19 pandemic. To maximise their contribution, it is important the social and occupational characteristics of the modern receptionist are understood, alongside their attitudes towards the role and their perceptions of the support and training they receive . Methods We used convenience and cross-sectional sampling to survey the demographic characteristics of receptionists and various aspects of their role and responsibilities. This included the training received, specific tasks performed, job satisfaction, the importance of the role, and their interaction with clinical and non-clinical colleagues. We also captured data on the characteristics of their practice including the number of GPs and location. Results A total of 70 participants completed the survey (16 postal and 54 online responses) of whom the majority were white (97.2%), female (98.6%), and aged 40 and over (56.7%). The majority of the training focussed on customer service (72.9%), telephone (64.3%), and medical administration skills (58.6%). Just over a quarter had received training in basic triage (25.7%). A standard multiple regression model revealed that the strongest predictor of satisfaction was support from practice GPs (β = .65, p <.001) there were also significant positive correlations between satisfaction and appreciation from GPs, r(68) = .609, p < .001. Conclusion This study has provided a much-needed update on the demographics, duties, and job satisfaction of GP receptionists. The need for diversification of the workforce to reflect the range of primary care patients warrants consideration in light of continuing variation in access along lines of gender andethnicity. Training continues to focus on administrative duties not on the clinically relevant aspects of their role such as triage.